2018
DOI: 10.4088/pcc.17m02156
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Follow-Up in First-Episode Psychosis

Abstract: Although Canada is often perceived as tolerant of diversity, our data regarding poor follow-up in black patients indicate similar problems to those reported in the United Kingdom and United States. Clinicians may have low expectations for visible minority patients and thus notice more consistently when these patients adhere to treatment. This is the first study to examine ethnic differences in adherence to first-episode psychosis follow-up in a Canadian setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…outpatient programs). African-Caribbean patients with psychosis have been found to undergo more police or ambulance referrals to the Emergency Department when psychotic (Jarvis et al, 2005), report more social coercion than members of other immigrant groups (Tran et al, 2019), have less general practitioner involvement (Anderson et al, 2015; Rotenberg et al, 2017) and have worse follow-up in comparison to other patient groups (Anderson, 2018; Nikolitch et al, 2018). There is still a paucity of research on coercive intervention, especially among FEP patients in the Canadian context where there has been an assumption of multiculturalism and tolerance for minorities (Anderson et al, 2014).…”
Section: Blackness and Psychosismentioning
confidence: 99%
“…outpatient programs). African-Caribbean patients with psychosis have been found to undergo more police or ambulance referrals to the Emergency Department when psychotic (Jarvis et al, 2005), report more social coercion than members of other immigrant groups (Tran et al, 2019), have less general practitioner involvement (Anderson et al, 2015; Rotenberg et al, 2017) and have worse follow-up in comparison to other patient groups (Anderson, 2018; Nikolitch et al, 2018). There is still a paucity of research on coercive intervention, especially among FEP patients in the Canadian context where there has been an assumption of multiculturalism and tolerance for minorities (Anderson et al, 2014).…”
Section: Blackness and Psychosismentioning
confidence: 99%
“…Of the 15 studies, five focused primarily on Black individuals, 52 , 55 , 56 , 59 , 60 while three focused on immigrants, refugees and migrants, 51 , 62 , 63 and seven others focused on diverse ethnic populations. 49 , 50 , 53 , 54 , 57 , 58 , 61 …”
Section: Resultsmentioning
confidence: 99%
“…A single study explored the role of ethnicity in adherence to follow-up. 49 This mixed methods study focused on the quality of follow-up, in addition to interviewing case managers to research their perception of their patients’ adherence to various aspects of their treatment. They found that Black participants were 24% less likely to receive an effective follow-up compared to White participants ( P = 0.04).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations